Re-Thinking Table Salt Reduction in Bread with Halophyte Plant Solutions - Barroca, Maria João (2023)
Sodium intake higher than it is physiologically necessary has been associated with some non-communicable diseases such as hypertension, cardiovascular disease, and stroke. Bread is commonly consumed and is a major source of sodium in the human diet. Among the interventions to reduce the salt content in bread, the incorporation of salty taste halophyte powder could be a promising strategy. In the present work, Sarcocornia perennis was incorporated as a food ingredient to substitute the salt (sodium) of white wheat bread (1.2% NaCl/0.47% sodium, flour basis). Powdered dried S. perennis was incorporated into bread by replacing the same amount of sodium (0.47%, flour basis) and half of the sodium concentration (0.235%, flour basis), respectively, B100 and B50 bread samples. The bread samples were analyzed to evaluate the impact of the sodium chloride replacement by S. perennis powder on total baking loss, specific volume, crumb color, textural properties, microbial activity, nutritional and mineral composition and sensory evaluation. The incorporation of S. perennis increased the specific volume but had no relevant impact on the textural properties of bread. Furthermore, the substitution of sodium chloride by S. perennis powder allowed a more colored (greenish and yellowish) and dark crumb leading to a lower whiteness index. Compared with control bread, the addition of S. perennis powder promoted a significant increase of all bread’s nutrients and minerals, namely calcium, phosphor, iron, and manganese. Besides the improvement of bread quality, B100, and B50 bread samples were both sensorily well accepted and with similar scores to all the evaluated sensorial attributes. Moreover, the reduction of sodium to half (0.235% sodium (flour basis) in bread (B50) did not affect the acceptability of tasters, as compared with B100 (0.47% sodium (flour basis)). Both new bread formulation has microbiological quality as ready-to-eat product. However, taking into account greater stability over time for microbial spoilage, mainly caused by fungi and yeasts, B50 bread is more promising. The B50 bread sample is also a potential strategy to obtain a sodium reduction of 50% in bread, which could be essential to reduce the overall sodium daily intake and bring important economic and public health benefits.